2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4650377
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of physical activities in Taekwondo Pumsae

Abstract: Exercise is very important element for successful aging. Among many sports events, Korea is the suzerain of Taekwondo. When competing (Taekwondo Free Fighting) after learning Poomse as basic movements and inuring them, people compete with movements depending on situation. Among Poomses of Taekwondo, Taegeuk Poomse consists of very basic movements from 1 Jang to 8 Jang and they are for inuring to body. In order to prescribe Taegeuk Jang, which is the basic movement of Taekwondo that Korea is the suzerain, as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…This system uses eight sensors that present an output voltage according to the internal material resistance that changes when a mechanical force is applied to it. The system is microcontrolled and transmits data by wireless communication modules [82]. …”
Section: Applications Between Sports and Biomedical Areasmentioning
confidence: 99%
“…This system uses eight sensors that present an output voltage according to the internal material resistance that changes when a mechanical force is applied to it. The system is microcontrolled and transmits data by wireless communication modules [82]. …”
Section: Applications Between Sports and Biomedical Areasmentioning
confidence: 99%
“…Taekwondo is a very popular sport in our country because it is an olympic sport (Tel et al, 2001). In the literature, the contribution of Taekwondo sport to both physical and mental development is expressed (Lee et al, 2008). According to the competition rules of Taekwondo, athletes start and finish their competitions in one day.…”
Section: Introductionmentioning
confidence: 99%
“…Regular Taekwondo training reduces obesity, enhances neurotransmitter secretion, and increases the CBF velocity, all of which positively affect the SWB. Furthermore, Lee et al analyzed the average energy consumption when performing Poomsae, a unique training form of Taekwondo, and found that approximately 5.06 kcal/min of energy could be consumed; this suggests that Taekwondo training is an effective exercise type for promoting successful aging [19]. Furthermore, not only is Taekwondo a popular sport in Korea, but findings from several previous studies also demonstrate its greater effectiveness in improving the mental health and cognitive function as compared with other forms of exercise [18,20].…”
Section: Introductionmentioning
confidence: 99%